2020
DOI: 10.3390/medicina56080384
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the IFNG (rs2430561) Polymorphism and Metabolic Syndrome in Perimenopausal Women

Abstract: Background and Objectives: Metabolic syndrome (MetS) is a multiple risk factor for atherosclerosis, cardiovascular disease, type 2 diabetes and strokes. One-third of middle-age women are at risk of MetS, which predisposes them to type 2 diabetes and cardiovascular disease. Changes in the regulation of anti-inflammatory cytokines―which play an important role in pathologic processes―may contribute to inflammatory disorders. Cytokine polymorphisms are known to have an impact on gene expression. The purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…What is more, the presented results of the study indicate that soldiers living in cities exhibit a higher intensity of health behaviors in all categories compared to village residents. The result is consistent with the data available in the literature [8,20,26,27], in which the authors found a higher frequency of correct health behaviors in urban residents compared to village residents. This result may be related to the fact that the city offers greater opportunities and easier access to services aimed at promoting healthy lifestyles, such as a wide range of diet catering directly delivered home or workplace, a rich sports infrastructure (including, for example, an ever-expanding network of bicycle paths), various public events, such as family picnics dedicated to health and making residents aware of the impact of everyday, even the smallest behaviors on health.…”
Section: Discussionsupporting
confidence: 92%
“…What is more, the presented results of the study indicate that soldiers living in cities exhibit a higher intensity of health behaviors in all categories compared to village residents. The result is consistent with the data available in the literature [8,20,26,27], in which the authors found a higher frequency of correct health behaviors in urban residents compared to village residents. This result may be related to the fact that the city offers greater opportunities and easier access to services aimed at promoting healthy lifestyles, such as a wide range of diet catering directly delivered home or workplace, a rich sports infrastructure (including, for example, an ever-expanding network of bicycle paths), various public events, such as family picnics dedicated to health and making residents aware of the impact of everyday, even the smallest behaviors on health.…”
Section: Discussionsupporting
confidence: 92%
“…Demographic and social determinants of health behaviors include age, gender, marital status, education, and material situation [14,[19][20][21]. The results of this study show that gender, place of residence, marital status, and economic status did not significantly influence the levels of health behaviors reported in our cohort.…”
Section: Discussionmentioning
confidence: 64%